BabyByte: Formative Research to Inform the Development of an App to Improve Responsive Feeding Practices in Parents of Infants and Toddlers. (29th May 2020) - Mobley, Amy; Schoffman, Danielle Jake; Fedele, David; de Cola, Briana; Varela, Elder
Abstract: Objectives: Responsive feeding is associated with reduced risk of early childhood obesity. The objective of this qualitative study was to determine parents' preferred content and features for a mHealth app designed to improve responsive feeding practices. Methods: Parents of 0–2 year old children completed individual semi-structured interviews with a trained researcher. Interview questions were informed by the Technology Acceptance Model and parents provided feedback on preferred app content and features. An app prototype, BabyByte, was developed using the Marvel platform to discuss potential app features during the interview. Interviews were audio-recorded and transcribed verbatim. Transcripts were coded by two researchers using a thematic analysis approach and major themes were summarized. Results: Parents ( n  = 40) were, on average, 33.2 years old with the majority self-reporting as non-Hispanic white (53%), a bachelor's degree or higher education (62%), and low-income (53%). Half of the participants were fathers. Overall, the majority (85%) of parents indicated that they would be likely or very likely to use BabyByte. Themes revealed that parents were most interested in topics related to introducing new foods, feeding tips, example meals, recipes, and food allergy guidance. Features including personalized profile set-up, video content, goal setting, milestone tracking, ask an expert, discussion forum, and an app search box were noted as most important or helpful by parents. Convenient access, up-to-date content from a reputable and identifiable source, and incentives for completing modules were indicated as important benefits. Conclusions: Findings of this study are important considerations for the development of future mHealth tools for parents of infants and toddlers to improve responsive feeding practices and prevent early childhood obesity. Usability testing of BabyByte is currently in progress. Funding Sources: University of Florida CTSI.